Porcine Sapelovirus 3Cpro Inhibits the Production of Type I Interferon - Yin, Mengge; Wen, Wei; Wang, Haoyuan; Zhao, Qiongqiong; Zhu, Hechao; Chen, Huanchun; Li, Xiangmin; Qian, Ping (Frontiers in Cellular and Infection Microbiology, 2022)
Porcine sapelovirus (PSV) is the causative pathogen of reproductive obstacles, acute diarrhea, respiratory distress, or severe polioencephalomyelitis in swine. Nevertheless, the pathogenicity and pathogenic mechanism of PSV infection are not fully understood, which hinders disease prevention and control. In this study, we found that PSV was sensitive to type I interferon (IFN-β). However, PSV could not activate the IFN-β promoter and induce IFN-β mRNA expression, indicating that PSV has evolved an effective mechanism to block IFN-β production. Further study showed that PSV inhibited the production of IFN-β by cleaving mitochondrial antiviral signaling (MAVS) and degrading melanoma differentiation-associated gene 5 (MDA5) and TANK-binding kinase 1 (TBK1) through viral 3Cpro. In addition, our study demonstrated that PSV 3Cpro degrades MDA5 and TBK1 through its protease activity and cleaves MAVS through the caspase pathway. Collectively, our results revealed that PSV inhibits the production of type I interferon to escape host antiviral immunity through cleaving and degrading the adaptor molecules.